Organizational learning in hospitals: Evaluation of the implementation of IT-supported nursing documentation - Siegert, Tanja; Eberl, Ingeborg; Göhlich, Michael (Zeitschrift für Evidenz, Fortbildung und Qualitat im Gesundheitswesen, 2021)
Background: The present paper explores the introduction of computer-based nursing documentation in a hospital as an example of organizational learning viewed through the lens of organizational education. It provides insights into existing routines and patterns of nursing practice within the organization and seeks, in understanding them, to support organizational learning in hospital settings. The focus of this article is on the analysis of patterns of practice specific to the organization in order to derive the specific need for support of organizational learning for the hospital as an organization. Methods: A mixed-methods approach was used to record data, combining qualitative and quantitative techniques. Its theoretical focus draws on organizational education in examining organizational learning – a context in which the use of mixed-methods approaches, triangulation and multiperspectivity appeared to be best suited for the task. Results: The results demonstrate that the practical implementation of computer-based nursing documentation calls, alongside technical adaptations, for the consideration of organizational learning, defined as learning undertaken by a social unit comprising a range of groups with distinct interests. The key challenge to organizational learning consists in disrupting long established routines and standardizing new patterns of practice. Success in this endeavor requires time and space for employees’ dialog-based, cooperative exploration of the patterns previously in place. Conclusion/Originality: The literature on organizational learning provides numerous examples of members of organizations rupturing previous patterns and routines, yet few examples aimed at creating an understanding of existing practices, particularly in relation to hospital settings. This paper fills this lacuna by describing extant practices in such a setting and seeks to support organizational learning processes in this context.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Evaluation; Information technology; Nursing documentation; Organizational education; Organizational learning